The impact of information technology on the development of audit process :Review of accepted theories of IT by the auditors - *, ahmadmarei; Alheety, Prof. Dr. Sadun (IJRDO - Journal of Business Management, 2018)
For professional accountants and particularly auditors involved in information systems (IS) audits, Information technology (IT) is important. Reliance of businesses on computerized information systems is increasing. As such, auditors are now obliged to equip themselves with the knowledge and skills of IT. The current study uses the Unified Theory of Acceptance and Use of Technology (UTAUT) to enable the exploration of the impact of information technology on a development of the audit process from the perspective of auditors through the study on the relationship between IT and the acceptance and auditors. This study’s results are grounded on a literature on the performance expectancy which describes the advantage and rewards elements are paramount and play a main part in the intent to utilize and employ CAATs auditors. This suggests that auditor understands a greater grade of performance expectancy to the adoption of CAATs. According to the effort expectancy, the effect demonstrated a paramount positive relevance with the utilization grade of CAATs. This signifies that higher effort expectancy means higher auditor’s employment level of CAATs.